2013
DOI: 10.1111/jnc.12307
|View full text |Cite
|
Sign up to set email alerts
|

Hypoosmotic and glutamate‐induced swelling of bipolar cells in the rat retina: comparison with swelling of Müller glial cells

Abstract: Regulation of cellular volume is of great importance to avoid changes in neuronal excitability resulting from a decrease in the extracellular space volume. We compared the volume regulation of retinal glial (M€ uller) and neuronal (bipolar) cells under hypoosmotic and glutamate-stimulated conditions. Freshly isolated slices of the rat retina were superfused with a hypoosmotic solution (60% osmolarity; 4 min) or with a glutamate (1 mM)-containing isoosmotic solution (15 min), and the size changes of M€ uller an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…I t has been shown that Müller cells, but not bipolar cells, possess endogenous signaling mechanisms that prevent cellular swelling under hypoosmotic conditions [42]. In agreement with this study, somata of freshly isolated bipolar cells (Fig.…”
Section: Effects Of Ets On Osmotic Soma Swelling Of Bipolar Cellssupporting
confidence: 84%
See 4 more Smart Citations
“…I t has been shown that Müller cells, but not bipolar cells, possess endogenous signaling mechanisms that prevent cellular swelling under hypoosmotic conditions [42]. In agreement with this study, somata of freshly isolated bipolar cells (Fig.…”
Section: Effects Of Ets On Osmotic Soma Swelling Of Bipolar Cellssupporting
confidence: 84%
“…In addition, the outer processes of both cell types display different morphologies, i.e., bipolar cells have a short and thick dendritic tree which contacts the synapses in the outer plexiform layer whereas Müller cells have one relatively thin outer stem process which draws to the outer nuclear layer. In previous experiments, the cellular identity was additionally confirmed by immunohistochemical staining of retinal slices for the Müller cell marker glutamine synthetase and the bipolar cell marker protein kinase Cα [13,42].…”
Section: Animals and Experimental Diabetesmentioning
confidence: 90%
See 3 more Smart Citations